1988
DOI: 10.1159/000226533
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of Flour Infested with <i>Tribolium castaneum </i>using the Egyptian Toad <i>Bufo regularis </i>as a Biological Test Animal

Abstract: Feeding the Egyptian toad Bufo regularis for 14 weeks with flour infested for 1 year with Tribolium castaneum, at a dose level of 200 mg/50 g body weight, induced neoplasms in 22 out of 100 toads. These neoplasms comprise 22 primary hepatocellular carcinomas and 6 tumours in the kidney due to metastases from the primary hepatocellular carcinoma. It is speculated that the carcinogenicity of the flour used in this work is due to quinone derivatives secreted by the defensive glands of T. castaneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…El-Mofty et al [4,6,34] reported that, baking temperature did not reduce the carcinogenic effect of biscuits made from flour infested with T. castaneum beetles but the mutagenic effects on mice remains unclear after being contaminated flour had been cooked and consumed, and Tribolium spp. are the only storage pests producing carcinogenic and teratogenic contaminants.…”
Section: Effect Of T Castaneum Adult Emergence On Bqs (Sum Both Of Mmentioning
confidence: 99%
“…El-Mofty et al [4,6,34] reported that, baking temperature did not reduce the carcinogenic effect of biscuits made from flour infested with T. castaneum beetles but the mutagenic effects on mice remains unclear after being contaminated flour had been cooked and consumed, and Tribolium spp. are the only storage pests producing carcinogenic and teratogenic contaminants.…”
Section: Effect Of T Castaneum Adult Emergence On Bqs (Sum Both Of Mmentioning
confidence: 99%
“…Based on subjective results of animal observations, the above authors concluded that quinone exerts a toxic effect by disrupting the functioning of the respiratory system. El-Mofty et al (1988) investigated the carcinogenic effect of benzoquinones administered per os to Bufo regularis tadpoles. The experiment was carried out on mature tadpoles of both sexes, with body weight of around 50 g, divided into two groups (control and experimental) of 100 animals each.…”
Section: Carcinogenicity and Toxicitymentioning
confidence: 99%
“…In a previous investigation [5], the present authors induced hepatocellular carcinomas (22%) in B. reg ularis, force-fed with flour infested with T. cas taneum. These authors speculated that the carcinogen ic effect of the flour may be due to the quinoid se cretions of these beetles [5], This stimulated the au thors to investigate whether biscuits made of flour in fested with 7'.…”
Section: Discussionmentioning
confidence: 57%
“…These authors speculated that the carcinogen ic effect of the flour may be due to the quinoid se cretions of these beetles [5], This stimulated the au thors to investigate whether biscuits made of flour in fested with 7'. castaneum still retains its carcinogenic activity or whether the heat may remove this effect?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation